Feed intake and growth variability in salmonids - Koskela, Juha (1997)
This review summarises the results of studies on feed intake and growth rate variability in Baltic salmon (Salmo salar L.), brown trout (Salmo trutta L.) and rainbow trout (Oncorhynchus mykiss (Walbaum)) exposed to different temperature and feeding regimes under laboratory conditions. The feed intake and growth of the Baltic salmon increased as the temperature increased from 2°C to the thermal optima and decreased with further increases in temperature. Maximal feed intake and growth were observed at 17.5-18°C and 14.5-15.0°C, respectively. Models for feed intake and growth in relation to temperature are presented. Both Baltic salmon and brown trout were able forage and increase their weight and lipid reserves at low temperatures (2-6°C). In rainbow trout restricted foraging conditions led to the formation of dominance hierarchies. This resulted in increased interindividual variability in both food acquisition and growth rate. The feeding hierarchies were rapidly broken down once food availability was increased. Under conditions of constant low temperature and continuous light the rates of feed intake and growth in Baltic salmon and brown trout were not constant but tended to increase with time. Low rates of feed intake and growth tended to be linked to high interindividual variability. These results indicated the importance of feeding and growth heterogeneity on group growth performance.